Effets du programme « Des mots pour les maux » auprès d’élèves à risque ou présentant une dyslexie : une étude pilote - Turcotte Tousignant, Fanny Maude; Parent, Véronique; Dupuis, Gilles; Guay, Marie-Claude (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This exploratory study investigated the outcomes of the program “Des mots pour les maux”, a program adapted to French and aimed at re-educating different components of written language on graphophonological correspondences and spelling representations with six students with dyslexia or at risk of presenting such disorder. The study is divided into 2 phases which 6 measures are taken: Phase 1 (at the beginning of the study, and 3 and 6 weeks after standard orthopedagogical interventions) and phase 2 (8 weeks, 16 weeks and 24 weeks after introducing the program tested) in order to assess the skills before and after the introduction of the program. The results suggest some improvement regarding phonological correspondences in reading and, more importantly, orthographic representations in reading and spelling 16 weeks after using the program. This study has thus indicated that dyslexic or at-risk students could benefit from this program “Des mots pour les maux”.